2014
DOI: 10.1002/2014ja020275
|View full text |Cite
|
Sign up to set email alerts
|

Impact angle control of interplanetary shock geoeffectiveness

Abstract: We use Open Geospace General Circulation Model global MHD simulations to study the nightside magnetospheric, magnetotail, and ionospheric responses to interplanetary (IP) fast forward shocks. Three cases are presented in this study: two inclined oblique shocks, hereafter IOS-1 and IOS-2, where the latter has a Mach number twice stronger than the former. Both shocks have impact angles of 30• in relation to the Sun-Earth line. Lastly, we choose a frontal perpendicular shock, FPS, whose shock normal is along the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
96
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(132 citation statements)
references
References 67 publications
33
96
0
3
Order By: Relevance
“…They found that inclined strong shocks did not lead to cavity wave excitation, and only shocks with normal incidence did. Since the IP shock discussed here has very similar properties to the one simulated by Oliveira and Raeder (2014), with exactly the same shock impact angle, their conclusions support the argument of the lack of cavity mode excitation in observed in the event discussed in this paper.…”
Section: Discussion: a Possible Mechanism Of Ip Shock Impact On The Gsupporting
confidence: 83%
See 1 more Smart Citation
“…They found that inclined strong shocks did not lead to cavity wave excitation, and only shocks with normal incidence did. Since the IP shock discussed here has very similar properties to the one simulated by Oliveira and Raeder (2014), with exactly the same shock impact angle, their conclusions support the argument of the lack of cavity mode excitation in observed in the event discussed in this paper.…”
Section: Discussion: a Possible Mechanism Of Ip Shock Impact On The Gsupporting
confidence: 83%
“…In our opinion, a very rare occurrence of the global cavity mode is a natural consequence of a weak reflection of a large-scale MHD mode with scale size ~10 R E from a small target (Earth) with scale size ~1 R E . The lack of cavity mode excitation in our analysis may be supported by numerical MHD simulation of IP shock impacts on the magnetosphere with different normal orientations by Oliveira and Raeder (2014). These authors concluded that the shock impact angle plays a major role in effectively compressing the magnetosphere, thereby leading to a more favorable scenario for cavity mode excitation due to symmetric magnetosphere compression.…”
Section: Discussion: a Possible Mechanism Of Ip Shock Impact On The Gsupporting
confidence: 57%
“…As a consequence, ICME-driven sheaths contain layers of plasma and magnetic field that have accumulated at different times and from different sources. ICMEdriven sheaths are of great interest for solar-terrestrial studies as they are strong drivers of geomagnetic activity (e.g., Tsurutani et al, 1988;Huttunen et al, 2002;Huttunen and Koskinen, 2004;Siscoe et al, 2007;Kilpua et al, 2017, see also Echer et al, 2011;Oliveira and Raeder, 2014;Lugaz et al, 2016), and their shocks have a key role in the acceleration of solar energetic particles (e.g., Reames, 1999;Manchester et al, 2005). Similarly to planetary magnetosheaths (e.g., Soucek et al, 2008;Osmane et al, 2015), MM waves may have large-scale effects on ICME sheaths.…”
Section: M Ala-lahti Et Al: Mirror Mode Wave Occurrence In Icme-mentioning
confidence: 99%
“…Finally, in their simulations, a third perpendicular shock impacted the Earth's magnetosphere frontally, with the same Mach number of the first shock. Oliveira and Raeder [] found that the third shock was much more geoeffective than the other two because the shock was frontal, and the magnetosphere was compressed symmetrically on both north and south sides. This compression led then to the triggering of a strong auroral substorm not seen in the other cases.…”
Section: Introductionmentioning
confidence: 99%